Elevated intraocular pressure in children with acute lymphoblastic leukaemia: A prospective study. (4th December 2021) - Barzilai‐Birenboim, Shlomit; Elitzur, Sarah; Nirel, Ronit; Ehrenberg, Miriam; Zahavi, Alon; Avrahami, Galia; Gabbay, Itay E.; Gilad, Gil; Dotan, Gad; Izraeli, Shai; Daood, Rabeea Haj; Geffen, Noa
Summary: Most childhood acute lymphoblastic leukaemia (ALL) protocols include high‐dose steroid therapy. However, the known potential of high‐dose steroids to significantly elevate intraocular pressure (IOP) and lead to glaucomatous optic neuropathy has not been intensively investigated in children with ALL. Moreover, as children with ALL do not routinely undergo IOP measurements, the need for IOP monitoring and therapy is unknown. We prospectively measured IOP in 90 children with newly diagnosed ALL attending a tertiary paediatric haematology/oncology centre, at diagnosis and at the middle and end of induction therapy. Ocular hypertension (IOP > 21 mm Hg) at any time point was documented in 64 children (71%), and the prevalence increased during induction. Thirty‐six children (40%) had elevated IOP at ALL diagnosis before therapy initiation, and stratification to non‐standard ALL was a risk factor. IOP reduction therapy was administered to 13 children (14%); none required surgery. Values normalised in all cases. On multivariate logistic regression analysis, dexamethasone therapy was a significant risk factor for ocular hypertension. High body mass index was an additional risk factor in children with elevated IOP at ALL diagnosis. Routine evaluation of IOP during steroid therapy is very important in children with ALL to ensure early intervention which may prevent permanent ocular damage.